Solidaritas Global: Gerakan Kemanusiaan untuk Palestina di Indonesia - Kaslam, Kaslam (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2024)
The conflict between Palestine and Israel has been going on for centuries. Starting from the rivalry over claims to land in the Palestinian territory desired for the establishment of the state of Israel, this conflict has resulted in fierce battles and prolonged political tensions. Israeli settlements in the West Bank and Gaza Strip have become points of controversy, viewed as violations of international law. This article aims to analyze the forms of global solidarity for Palestine, particularly those occurring in Indonesia. Using descriptive qualitative research and a library research approach, this article draws on data from various valid media sources. The findings show that the impact of the Palestine-Israel conflict is not only felt locally but also spreads worldwide, including to Indonesia. Indonesia, as the country with the largest Muslim population, has a strong emotional involvement in the conflict. Solidarity with Palestine is a primary concern in Indonesia’s foreign policy, with strong support from the government and the populace. Solidarity movements for Palestine are active in Indonesia, involving various political groups, civil society organizations, religious institutions, and student groups. Mass actions and public campaigns are regularly held to condemn Israeli actions and support Palestinian independence. Furthermore, the role of social media is significant in shaping opinions on the concerns in Palestine. Overall, these events have wide-ranging impacts, affecting Indonesian politics and society, and drawing international attention to human rights issues and global peace